Key Factors Impacting Profitability in Indonesian Commercial Banks: Financial Ratio, Macroeconomic, and Ownership Structure - Amalia Mega Berliana; Grecia Alvionita Simanjorang; Villia Nikmatul Khasanah; Henny Setyo Lestari; Farah Margaretha (Universitas KH. Abdul Chalim Mojokerto, 2025)
Profitability is essential for assessing company performance and attracting investors. This study aims to examine the effect of non-interest income, size, loan loss provision, capital adequacy ratio, overheads, non-performing loans, inflation, interest rate, and foreign ownership on the profitability of commercial banks in Indonesia. Using a quantitative approach, secondary data from the Indonesia Stock Exchange, Central Bureau of Statistics, Bank Indonesia, and company websites were analyzed over seven years (2017-2023) from 32 commercial banks, resulting in 224 financial statement data points. Panel data regression analysis with Eviews 12 was employed. The results indicate that non-interest income, size, inflation, interest rate, and foreign ownership do not significantly affect profitability. However, loan loss provision, capital adequacy ratio, overheads, and non-performing loans significantly impact profitability. These findings highlight the importance of managing problematic loans, maintaining a robust capital adequacy ratio, and improving operational efficiency to enhance profitability. The study suggests that company managers should also consider other factors such as financing decisions, asset utilization, tangibility, sales growth, and age to maximize profitability. Future research should explore different sectors and extend the study period to identify additional factors influencing corporate profitability, thereby providing deeper insights for strategic decision-making to improve financial performance.